The evaluation of an educational intervention based on Pender's health promotion model for patients with myocardial infarction. Issue 1 (2nd January 2022) - Moshki, Mahdi; Mohammadipour, Fatemeh; Gholami, Mohammad; Heydari, Fardin; Bayat, Mahboobeh
ABSTRACT: Despite advances in drug treatment and surgical interventions for the care of myocardial infarction, it has a high morbidity and mortality rate in Iran. In order to stop or reverse this trend, educational interventions based on various models are necessary. To determine the effect of an educational intervention based on Pender's health promotion model on lifestyle, related factors, and clinical outcomes of patients with myocardial infarction, a clinical trial study was conducted. Patients were randomly allocated to two groups of educational intervention based on Pender's model (n = 50) and the control group (n = 50). Educational sessions included eight 45-minute sessions held twice per week. Data gathering instruments were completed by the groups before and three months after intervention. The total mean of lifestyle, cardiac knowledge, perceived benefits of behavior, cholesterol, and triglycerides rates were significantly improved in the intervention group. Evaluation of the findings confirmed the effect of this educational model on healthy behaviors of patients with Myocardial Infarction.